Clinical Characteristics and Outcomes of Older Patients with Coronavirus Disease 2019 (COVID-19) in Wuhan, China: A Single-Centered, Retrospective Study. (11th April 2020) - Chen, TieLong; Dai, Zhe; Mo, Pingzheng; Li, Xinyu; Ma, Zhiyong; Song, Shihui; Chen, Xiaoping; Luo, Mingqi; Liang, Ke; Gao, Shicheng; Zhang, Yongxi; Deng, Liping; et al.
Abstract: Background: In December 2019, the coronavirus disease 2019 (COVID-19) emerged in Wuhan city and spread rapidly throughout China and the world. In this study, we aimed to describe the clinical course and outcomes of older patients with COVID-19. Methods: This is a retrospective investigation of hospitalized older patients with confirmed COVID-19 at Zhongnan Hospital of Wuhan University from January 1, 2020, to February 10, 2020. Results: In total, 203 patients were diagnosed with COVID-19, with a median age of 54 years (interquartile range, 41–68; range, 20–91 years). Men accounted for 108 (53.2%) of the cases, and 55 patients (27.1%) were more than 65 years of age. Among patients who were 65 years and older, the mortality rate was 34.5% (19/55), which was significantly higher than that of the younger patients at 4.7% (7/148). Common symptoms of older patients with COVID-19 included fever (94.5%; n = 52), dry cough (69.1%; n = 38), and chest distress (63.6%; n = 35). Compared with young patients, older patients had more laboratory abnormalities and comorbidities. Through a multivariate analysis of the causes of death in older patients, we found that males, comorbidities, time from disease onset to hospitalization, abnormal kidney function, and elevated procalcitonin levels were all significantly associated with death. Conclusions: In the recent outbreak of COVID-19, our local hospital in Wuhan found that patients aged 65 and older had greater initial comorbidities, more severe symptoms, and were more likely to experience multiorgan involvement and death, as compared to younger patients.